2006
DOI: 10.1093/ndt/gfl530
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early renal function parameters for the prediction of 5-year graft survival after kidney transplantation

Abstract: Routine parameters for monitoring of EGF display a threshold effect allowing accurate prediction of 5-year graft survival at the earliest point in time. The quantitative threshold levels for an optimum discriminatory power require validation in a larger, preferably multicentre database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
1
25
1
1
Order By: Relevance
“…However, we show that the model using the definition in days of DGF (Ͻ or Ն6 days) enhances the number of explanatory variables and thus is probably more interesting for the physician. Moreover, a recent study of Schnuelle showed that dialysis requirement posttransplantation was not a significant explanatory variable in the multivariate analysis of five-year graft survival contrary to the 1-week graft function, confirming our choice of DGF definition with the creatinine clearance (35).…”
Section: Discussionsupporting
confidence: 67%
“…However, we show that the model using the definition in days of DGF (Ͻ or Ն6 days) enhances the number of explanatory variables and thus is probably more interesting for the physician. Moreover, a recent study of Schnuelle showed that dialysis requirement posttransplantation was not a significant explanatory variable in the multivariate analysis of five-year graft survival contrary to the 1-week graft function, confirming our choice of DGF definition with the creatinine clearance (35).…”
Section: Discussionsupporting
confidence: 67%
“…A score based on the combination of serum creatinine at post-KT day 7 (Cr7) and urine output at post-KT day 1(UO1) was proposed (Schnuelle et al, 2007).…”
Section: Combined Definition a Cr7 And Uo1mentioning
confidence: 99%
“…Survival curves of the respective controls not meeting these requirements are displayed in light-colored lines. Taken from Schnuelle et al, 2007. b. A definition of DGF obtainable within 6 hours after KT was proposed (Gonwa et al, 2002).…”
Section: Understanding the Complexities Of Kidney Transplantation 230mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Early renal function parameters such as urine output during 24 hours after transplantation and serum creatinine (sCr) after 1 week are also valuable in estimation of long-term survival. 7 Radionuclide measurements of renal function are conveniently divided into 3 categories corresponding to the classic 3 phases of the renogram. The first phase corresponds to transit of a bolus tracer through the renal blood vessels.…”
mentioning
confidence: 99%